PERAN REPUTASI PERUSAHAAN SEBAGAI PEMEDIASI PADA PENGARUH PENGUNGKAPAN WEBSITE CSR TERHADAP KINERJA BISNIS PERUSAHAAN - Azzahra, Nabila; Widiastuty, Erna (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
This study examines the role of company reputation as a mediator in the broad influence of CSR website disclosure on company business performance. The sample consists of non-financial public companies listed on the Indonesia Stock Exchange for the 2017-2021. Sampling was done using a purposive method and obtained 775 firm-year samples. Sources of research data come from the company's annual report, the company's website, and the Eikon Refinitive Datastream. Hypothesis testing using SEM-PLS with WarpPLS 7.0 software. This study's results indicate that corporate reputation's role mediates the broad influence of CSR website disclosure on corporate business performance. The result shows vary. The results of this study have implications that CSR website disclosure must be used as a long-term strategy that is in line with POJK regulation no. 8/POJK.04/2015. Furthermore, regulators can increase regulations regarding what areas must be disclosed on the CSR website.